FUZZY CLUSTERING ALGORITHM AND ITS APPLICATION ON CARCINOMA TISSUE (2011)
This invention relates to a method for identifying and classifying carcinomas on the skin of a subject by a FTIR or Raman spectrometer coupled with a micro-imaging system.